Novel pharmacological and dietary approaches to target mTOR in B-cell acute lymphoblastic leukemia - Buono, Roberta; Alhaddad, Muneera; Fruman, David A. (Frontiers in Oncology, 2023)
High-risk subtypes of B-cell acute lymphoblastic leukemia (B-ALL) are frequently associated with aberrant activation of tyrosine kinases (TKs). These include Ph+ B-ALL driven by BCR-ABL, and Ph-like B-ALL that carries other chromosomal rearrangements and/or gene mutations that activate TK signaling. Currently, the tyrosine kinase inhibitor (TKI) dasatinib is added to chemotherapy as standard of care in Ph+ B-ALL, and TKIs are being tested in clinical trials for Ph-like B-ALL. However, growth factors and nutrients in the leukemia microenvironment can support cell cycle and survival even in cells treated with TKIs targeting the driving oncogene. These stimuli converge on the kinase mTOR, whose elevated activity is associated with poor prognosis. In preclinical models of Ph+ and Ph-like B-ALL, mTOR inhibitors strongly enhance the anti-leukemic efficacy of TKIs. Despite this strong conceptual basis for targeting mTOR in B-ALL, the first two generations of mTOR inhibitors tested clinically (rapalogs and mTOR kinase inhibitors) have not demonstrated a clear therapeutic window. The aim of this review is to introduce new therapeutic strategies to the management of Ph-like B-ALL. We discuss novel approaches to targeting mTOR in B-ALL with potential to overcome the limitations of previous mTOR inhibitor classes. One approach is to apply third-generation bi-steric inhibitors that are selective for mTOR complex-1 (mTORC1) and show preclinical efficacy with intermittent dosing. A distinct, non-pharmacological approach is to use nutrient restriction to target signaling and metabolic dependencies in malignant B-ALL cells. These two new approaches could potentiate the TKI efficacy in Ph-like leukemia and improve survival.